THE EFFECT OF PROFITABILITY, LEVERAGE, COMPANY SIZE, AND SALES GROWTH ON TAX AVOIDANCE OF RETAIL COMPANIES LISTED ON THE IDX - Indri Kurnia Putri (International Research of Multidisciplinary Analysis, 2023)
This study aims to determine the effect of perofitability, leverage, company size, and sales growth on tax avoidance of retail companies listed on the IDX in 2016-2020. The analytical method used in this study is quantitative analysis method. The tool used is factor analysis using the Eviews9 tool with panel data regression models. 8 companies met the sampling criteria. The results of this study show that profitability has no effect while leverage, company size and sales growth affect tax avoidance. There is a significant influence between variables simultaneously with F-Statistic 16.58448. The R-Squared coefficient of determination is 0.799841 or 79% of the dependent variable, this shows that the variable is unable to explain the variation of the variable and other factors outside regression influence the remaining 21%.